Factors associated with students’ unwillingness to voluntarily donate blood in the Eastern Region of Ghana - Foster Amponsah-Manu; Augustine Badu; Yubraj Acharya; Augustine kyere; Philomena Quayson; Jocelyn Asibey; Samuel Attua; Richmond Afrifa; Eunice Serwaa Kegyeda; Samuel Morton; Richmond Ampofo; Gloria Akofa Quarshie; et al. (PLoS ONE, 2026)
Background The World Health Organisation advocates for voluntary blood donation (BD) as a sustainable means of maintaining adequate blood availability in healthcare facilities globally. However, the Eastern Region of Ghana experiences low voluntary BD rates among students. The study aimed to determine factors associated with this pattern, conceptualising unwillingness as a key determinant of low voluntary BD. Method The analytical cross-sectional study was conducted from July to August 2025. Respondents were engaged with a structured questionnaire which gathered information on demographic characteristics, prior donation experience, knowledge about blood donation, sociocultural influences, institutional and logistical factors. Descriptive, Chi-square and multivariable regression analyses were done with Stata® version 15.0. Statistical significance was assumed at P-values <0.05. Results A total of 2,200 students participated in the study, and 40.3% (887/2,200) of them were unwilling to voluntarily donate blood (VDB). Unwillingness was significantly associated with perceived ineligibility for blood donation (aOR 3.45, 95% CI: 2.63–4.52), belief that blood donation is unsafe (aOR 1.98, 95% CI: 1.56–2.49), low knowledge about blood donation (aOR 1.68, 95% CI: 1.05–2.69), and discouragement by cultural or religious background (aOR 1.85, 95% CI: 1.25–2.73). Institutional and logistical barriers including long waiting times (aOR 4.31, 95% CI: 2.14–8.70), lack of incentives (aOR 3.85, 95% CI: 1.85–8.02) and inconvenient donation locations (aOR 3.04, 95% CI: 1.51–6.09), were also independently associated with unwillingness. Free health check-ups were the most preferred incentive. Conclusion The study revealed important factors influencing students’ unwillingness to VDB. Addressing misconceptions, improving education on eligibility and safety, and reducing logistical barriers may enhance students’ willingness and potentially increase voluntary BD rate.